Evaluation of Reactivity of Monoclonal Antibodies Against Omp25 of Brucella spp. - Yang, Xin; He, Zuoping; Zhang, Guoxia; Lu, Jinhui; Zhang, Hui; Ren, Hui; Tian, Yanjun; Yang, Heng; Chen, Chuangfu; Li, Linhai; Fu, Yongshui; Allain, Jean-Pierre; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Brucellosis is a serious zoonosis occurring mainly in developing countries, and its diagnosis is largely dependent on serologic detection and bacterial culture. In this study, we developed the murine monoclonal antibodies (mAbs) against a conserved and major outer membrane protein 25 (Omp25) of Brucella species (B. spp.) for use in clinical diagnosis. The mAbs to Omp25 were produced by hybridoma technique, which were utilized for developing various immunoassays for detection of Brucellae, including Western blot (WB), enzyme-linked immunosorbent assay (ELISA), immunochemical staining (ICS), immunofluorescence staining (IFS), and flow cytometry assay (FCM). A number of five mAbs (2B10, 4A12, 4F10, 6C12, and 8F3) specific to Omp25 were selected, including 2 IgG1, 2 IgG2a, and 1 IgG2b. Among them, mAbs 6C12, 8F3, and 4A12 reacted highly with B. melitensis (M5-90), B. abortus (S19, 104M, and 2308), and B. suis strain (S2). No cross-reactivity with Yersinia enterocolitica O:9, Salmonella spp., and Escherichia coli was found. By mapping Omp25 epitopes, mAb 6C12 was found as reacting with a semi-conformational epitope, and mAbs 4A12 and 8F3 as recognizing a different linear epitope, respectively. The paired mAbs were tested for detecting Brucella species, suggesting that 8F3 was suitable for solid phase capture and 6C12 or 4A12 was suitable for conjugation with HRP for detection of Brucella Omp25 in ELISA. The FCM was established by mAb 6C12 for detecting intracellular Brucellae-infected peripheral blood mononuclear cells (PBMCs) from brucellosis patients. In conclusion, mAbs against Omp25 are precious reagents for detection of Brucellae in clinical samples with various immunoassays. mAb 6C12-based FCM could be potentially used for the monitoring of therapeutic efficacy for brucellosis in clinical practice.